Synthesis and cytotoxicity study of magnesium ferrite-gold core-shell nanoparticles - Jeeranan Nonkumwong (2018)
© 2015 Elsevier B.V. In this work, the core-magnesium ferrite (MgFe2O4) nanoparticles were prepared by hydrothermal technique. Completed gold (Au) shell coating on the surfaces of MgFe2O4nanoparticles was obtained by varying core/shell ratios via a reduction method. Phase identification, morphological evolution, optical properties, magnetic properties and cytotoxicity to mammalian cells of these MgFe2O4core coated with Au nanoparticles were examined by using a combination of X-ray diffraction, scanning electron microscopy, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy, UV-visible spectroscopy (UV-vis), vibrating sample magnetometry and resazurin microplate assay techniques. In general, TEM images revealed different sizes of the core-shell nanoparticles generated from various core/shell ratios and confirmed the completed Au shell coating on MgFe2O4core nanoparticles via suitable core/shell ratio with particle size less than 100 nm. The core-shell nanoparticle size and the quality of coating influence the optical properties of the products. The UV-vis spectra of complete coated MgFe2O4-Au core-shell nanoparticles exhibit the absorption bands in the near-Infrared (NIR) region indicating high potential for therapeutic applications. Based on the magnetic property measurement, it was found that the obtained MgFe2O4-Au core-shell nanoparticles still exhibit superparamagnetism with lower saturation magnetization value, compared with MgFe2O4core. Both of MgFe2O4and MgFe2O4-Au core-shell also showed in vitro non-cytotoxicity to mouse areola fibroblast (L-929) cell line.